The wheat sector in Ethiopia: Current status and key challenges for future value chain development - Samuel Gebreselassie; Mekbib G. Haile; Matthias Kalkuhl (University of Bonn, Center for Development Research (ZEF), 2017)
This paper provides a general overview of the current status and key challenges of the Ethiopian wheat value chain. Wheat is an important staple food crop in Ethiopia. Improving wheat production and productivity is therefore a key part of the agenda in the Ethiopian government's food security policy programs. Policy interventions that aim at improving wheat production or agricultural production for that matter, however, require interventions beyond the farm-at the whole wheat value chain. Both domestic production and import-the two key sources of wheat grain supply to the Ethiopian wheat value chain-have shown a substantial increase since the mid-1990s. Yet, a steady increase in domestic wheat consumption has resulted in rising wheat and wheat product prices over the past two decades. For instance, wheat grain, wheat flour as well as wheat bread prices have all more than doubled between 2000 and 2013. Using a qualitative survey of selected wheat value chain actors and a review of existing literature, this study provides an overview of the wheat value chain, institutional and marketing arrangements, and trader behaviour of wheat value chain actors in Ethiopia. The wheat value chain consists of multiple actors that include several smallholder farmers and the Ethiopian grain trade enterprise (EGTE) at the upstream and urban and rural consumers at the other end. The study stresses the need for formulation of market-enhancing policies, such as quality control and dispute settlement mechanisms as well as better access to market information, to improve wheat productivity as well as marketing efficiency.
Keywords: L11; M31; Q02; Q11; Q13; 330; Value chain; wheat; grain market; food prices; price transmission; Ethiopia